Gifted children of color around the world : diverse needs, exemplary practices, and directions for the future - Davis, Joy Lawson, 1953-; Moore, James L., III (Advances in race and ethnicity in education, 2016)
This edited volume sheds light on the unique challenges, trends, and intersecting issues related to identifying intellectual potential of children of color around the world, providing access to appropriate curriculum and instructional opportunities, addressing the professional capacities of teachers working with these students, and the role of diverse families and communities in the talent development process in these communities.